2009
DOI: 10.1038/nature08242
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Rho GTPase activities during cell protrusion

Abstract: The GTPases Rac1, RhoA and Cdc42 act in concert to control cytoskeleton dynamics1-3. Recent biosensor studies have shown that all three GTPases are activated at the front of migrating cells4-7 and biochemical evidence suggests that they may regulate one another: Cdc42 can activate Rac18, and Rac1 and RhoA are mutually inhibitory9-12. However, their spatiotemporal coordination, at the seconds and single micron dimensions typical of individual protrusion events, remains unknown. Here, we examine GTPase coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

73
1,111
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 891 publications
(1,191 citation statements)
references
References 29 publications
73
1,111
7
Order By: Relevance
“…All three proteins are involved in actin polymerization and have been shown to be localized in the cell leading edge during protrusion formation [18][19][20][21][22]. We found both increasing (V12Rac1) and lowering (N17Rac1) activity resulted in defective heterotypic CIL.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…All three proteins are involved in actin polymerization and have been shown to be localized in the cell leading edge during protrusion formation [18][19][20][21][22]. We found both increasing (V12Rac1) and lowering (N17Rac1) activity resulted in defective heterotypic CIL.…”
Section: Discussionmentioning
confidence: 69%
“…While RhoA activation occurs as a band 2 lm from the leading edge, Cdc42 and Rac1 peak 1.8 lm behind the leading edge of the protrusion close to the sites of maturing adhesions. Hence, the authors suggest the latter two GTPases may regulate adhesion dynamics [20]. If similar spatiotemporal coordination occurs between RhoA and Rac1 in the protrusions of NIH3T3 cells, increased RhoA activity could be affecting heterotypic CIL by disrupting the retraction phase of the cycle.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There is evidence that Rac1 can stabilize cortical actin to promote junctional stability in endothelial cells 22, 23. In addition, coordinated, cyclic activity of Rac1 and RhoA are known to control the protrusion and withdrawal of cell protrusions 83. Recently, we reported that treatment of endothelial cells with either thrombin or a selective inhibitor of Rac1 can decrease the protrusion frequency of small, local lamellipodia in conjunction with disruption of the endothelial barrier 17.…”
Section: Discussionmentioning
confidence: 99%